Justiça restaurativa e seu alcance sociojurídico: um paradigma em construção nas tessituras do resgate da dignidade da pessoa humana e da inclusão social. - CARVALHO, Tereza Cristina Soares da Fonseca (2021)
In the last forty years, contemporaneity has been lived as a historical moment, permeated by metamorphoses, paradoxes and dilemmas. One of the dilemmas of these times is violence, which permeates the social context, as an expression-synthesis of contemporary issues, challenging the Social and Human Sciences and, particularly, the Legal Sciences. In view of the magnitude of the violence, the traditional paradigm of Justice, known as Retributive Justice, is not showing itself capable of, in isolation, providing effective responses to the population's desires, prisoners of fear and insecurity. In this context, Restorative Justice has been constituting itself as an alternative paradigm in different countries. In Brazil, this humanized approach to Justice is consolidated, both in terms of formulations in the legal field, as well as in experiences in different areas of the judicial system, configuring itself as an investigation theme and as a way to face violence. It is based on the affirmation of human rights and respect for the dignity of the human person. In this sense, the theories of the Ethics of Alterity and the Constitutional Principle of the Fraternity are revealed as privileged ways of expanding its philosophical and legal bases. The dissertation, now presented, assumes Restorative Justice as a research theme, having as a guideline the analysis of its socio-legal scope in the fabric of Brazilian society. Thus, it seeks to understand to what extent this humanized paradigm of Justice contributes to the social inclusion of the different subjects involved in criminal conflicts. In the investigative dynamics, this dissertation defines Open and Critical Rationalism as methodological guidance. It is configured as a predominantly qualitative research, of a theoretical-analytical nature, with quantitative contributions. In this perspective, bibliographic research and documentary research are carried out, aimed at expanding the philosophical - legal bases of Restorative Justice and for delineating experiences in this field, especially in São Luís - Maranhão and Brasília-DF. In a systematic and methodical approach, we conclude with the outline of emerging trends in the process of building the paradigm of Restorative Justice, in the Brazilian context, in this 21st century. Among these trends, the following stand out: the restorative matrix has been the object of reflections and experiences, with academic productions and debates in the institutions of the justice system; this restorative matrix is not intended to be a substitute path for retributive justice, but a complementary one; its socio-legal reach is expressed in close relationship with the process of social inclusion, consolidating itself significantly in the field of adolescence; the restorative paradigm requires interinstitutional and multidisciplinary action, having an organic link with affirmative and emancipatory public policies.